KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS THYROID NODULE AMONG CLIENTS ATTENDING PRIMARY HEALTH CENTERS IN RASAFA HEALTH DIRECTORATE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Thyroid nodules are commonly encountered in clinical practice, with a significant variation in their size and potential malignancy. There is a public knowledge gap about thyroid nodules complicating timely diagnosis and effective management. The study aimed to evaluate the knowledge, attitudes, and practices regarding thyroid nodules among clients at primary health centers in Rasafa, Baghdad, Iraq. A descriptive cross-sectional design conducted from January to July 2024 at selected primary health centers in the Rasafa Center Directorate, Baghdad. A structured questionnaire was administered to 250 randomly selected. The study included adults aged 18 years and above, excluding those with a history of thyroid disorders. The study included 250 participants, with a majority being female (66.4%) and under 35 years old (69.6%). Knowledge of thyroid nodules was mostly fair, with 62.0% scoring between 5 and 8, while only 25.2% had good knowledge. Education level and income were significantly associated with better knowledge scores (P = 0.0001). In terms of attitudes, 82.4% of participants exhibited a positive attitude towards thyroid nodules. For practices, 51.2% followed up regularly with their doctor, but only 31.2% had undergone diagnostic tests. Medication adherence was relatively high at 77.2%, but lifestyle modifications were less common (34.8%).The study concluded that while participants had general awareness of thyroid nodules, there were significant gaps in understanding symptoms, complications, and diagnostic methods. Adherence to recommended practices was lacking. These findings highlight the need for tailored educational programs and improved follow-up strategies to enhance thyroid nodule management.